Geoarqueology: Interdisciplinary explanations for the archaeological research - Acevedo, Benjamín (2014)
Geoarchaeological research involves interdisciplinary work. The objectives, theoretical framework, methodological approach and the final analysis are built together from archeology and disciplines within the earth sciences to better understand what life was like in the past. The Geological Journal of Central America is a journal to present joint work between geoscientists and archaeologists. Together these fields can present a unique approach to material remains, expanding the range of issues, analysis and interpretations thereby brining new light to some of the traditional methods and techniques in archaeology